2012
DOI: 10.5751/es-04772-170219
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Comanagement in the Venice Lagoon? An Analysis of Current Water and Environmental Management Practices and Prospects for Change

Abstract: ABSTRACT. Adaptive comanagement (ACM) is often suggested as a way of handling the modern challenges of environmental governance, which include uncertainty and complexity. ACM is a novel combination of the learning dimension of adaptive management and the linkage dimension of comanagement. As has been suggested, there is a need for more insight on enabling policy environments for ACM success and failure. Picking up on this agenda we provide a case study of the world famous Venice lagoon in Italy. We address the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 51 publications
(45 reference statements)
1
30
0
Order By: Relevance
“…Finally, we found that, although all experiments produced unexpectedly low normative learning (although in line with previous learning studies [3,7,27,31]) the perspectives change dimension registered very differently among actor types: individual "citizen" actors were significantly more likely to record favourably for both normative learning variables. This result did not come through in the initial analysis because there were so few individual citizens involved (n = 9), who were predominantly found in the boundary experiments.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Finally, we found that, although all experiments produced unexpectedly low normative learning (although in line with previous learning studies [3,7,27,31]) the perspectives change dimension registered very differently among actor types: individual "citizen" actors were significantly more likely to record favourably for both normative learning variables. This result did not come through in the initial analysis because there were so few individual citizens involved (n = 9), who were predominantly found in the boundary experiments.…”
Section: Discussionsupporting
confidence: 64%
“…The factors are drawn from several sources [3,5,[18][19][20][21]. This typology has been used in several empirical studies to conceptualise and measure learning in collective settings relevant to environmental governance [3,27,30,31]. The first two learning types resonate strongly with the policy learning literature [27] whereas relational learning reflects the notions of understanding others' roles and capacities, which are developed in the social learning literature [28,32].…”
Section: Definition and Typology Of Policy Learningmentioning
confidence: 98%
“…efficient, for issues affecting entire communities at once, but they are also more likely to create certain lock-ins. Such lock-ins could be related to the sunk investments, to the knowledge and organization needed to build such infrastructure, which will want to sustain itself (see for example the case of large scale infrastructure for flood defense in Venice by Munaretto and Huitema 2012), and could also be related to the expectations of the population; in case of large-scale infrastructure they might start assuming that the infrastructure takes care of the issue and they do not need to do anything themselves (see, for example, Engel et al 2014). In other words, efficiency thinking might lead to greater government involvement, which might subsequently lead to a greater recourse to technical solutions, but whether this is more resilient in the long term is unclear.…”
Section: Adaptation Governance Choices: Summary and A Research Agendamentioning
confidence: 99%
“…There may be confusion within the concept of normative learning because previous studies similarly have not been able to assess or measure it (Haug et al 2011, Munaretto and Huitema 2012. A question arises of what changes in norms, views, or paradigms are relevant.…”
Section: Adaptive Comanagement (Acm) and Invasive Species Issuesmentioning
confidence: 99%